Functional significance of myocardial activity at 18F-FAPI PET/CT in hypertrophic cardiomyopathy identified by cardiac magnetic resonance feature-tracking strain analysis. - Zhang, Yu; Dong, Zhixiang; Wang, Li; Wang, Yi-Lu; Chen, Bi-Xi; Su, Yao; Zhao, Shihua; Yang, Min-Fu (European Journal of Nuclear Medicine & Molecular Imaging, 2023)
Purpose: This study aimed to evaluate the functional significance of 18F-labeled fibroblast activation protein inhibitor (18F-FAPI) activity in hypertrophic cardiomyopathy (HCM) by comparison with cardiac magnetic resonance feature-tracking (CMR-FT) strain analysis. Methods: A total of 49 HCM patients were included in this study. Two independent control groups of healthy participants with a matched age and sex to the HCM patients were also enrolled. Left ventricular (LV) 18F-FAPI activity was analyzed for extent (FAPI%) and intensity (maximum target-to-background ratio, TBRmax). The CMR tissue characterization parameters of the LV included late gadolinium enhancement, native T1 value, and extracellular volume fraction. LV strain analysis was performed in radial, circumferential, and longitudinal peak strains (PS). Results: Intense LV myocardial 18F-FAPI uptake was observed in HCM patients, whereas no obvious uptake was detected in healthy participants (median TBRmax, 9.1 vs. 1.2, p < 0.001). The strain parameters of HCM patients, compared with healthy participants, were significantly impaired (mean radial PS, 23.5 vs. 36.0, mean circumferential PS, −14.5 vs. −20.0, and mean longitudinal PS, −9.9 vs. −16.0, all p < 0.001). At segmental levels, there was a moderate correlation between 18F-FAPI activity and strain parameters. The number of positive 18F-FAPI uptake segments (n = 653) was higher than that of hypertrophic segments (n = 190) and positive CMR tissue characterization segments (n = 525) (all p < 0.001). In segments with negative CMR tissue characterization findings, the strain capacity of positive 18F-FAPI uptake segments was lower than that of negative 18F-FAPI uptake segments (median radial PS, 30.5 vs. 36.1, p = 0.026 and median circumferential PS, −18.4 vs. −19.7, p = 0.041). Conclusion: 18F-FAPI imaging can partially reflect the potential strain reduction in HCM patients. 18F-FAPI imaging detects more involved myocardium than CMR tissue characterization techniques, and the additionally identified myocardium has impaired strain capacity.